Statistics of Square-tiled Surfaces - Shrestha, Sunrose. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Mathematics.; Advisor: Moon Duchin.; Committee: Boris Hasselblatt, Larry Guth, and Thomas Weighill.; Keyword: Mathematics.